“French Teachers Can Figure It Out”: Understanding French as a Second Language (FSL) Teachers’ Work in the Context of the COVID-19 Pandemic - Smith, Cameron W.; Arnott, Stephanie (Canadian Journal of Applied Linguistics / Revue canadienne de linguistique appliquée)

(untitled) (University of New Brunswick, 2022)
In 2020, the coronavirus (COVID-19) pandemic forced teachers in Ontario to move online. Since then, teaching online or in hybrid models has been common across the province. To understand how French as a Second Language (FSL) teachers navigated these spaces, four Ontario French teachers were interviewed about their experience using educational technology and teaching online. Findings were analyzed in light of Hargreaves and Fullan’s (2020) reframing of classic understandings of teachers’ work in the context of the global pandemic. Findings show that factors influencing these teachers’ professional capital reflect common concerns among Canadian educators, alongside those specific to the FSL context. Participants' professional marginalization and seclusion demonstrates the importance of both the psychic rewards of teaching and cultures of collaboration. Ongoing efforts to capture ways in which teaching FSL has been shaped by the pandemic experience, therefore, require looking beyond individual classrooms to connected systems and systematic efforts of reform.